Investigando aspectos históricos e filosóficos da Física Moderna e Contemporânea em um curso de Licenciatura em Física: Diálogo entre as competências presentes no Projeto Pedagógico de Curso e e no Exame Nacional de Desempenho dos Estudantes (ENADE) - Silva, Rafaella Martins da (2019)
In this work, we investigated the implications of external evaluations in a Physics degree course at a state public institution. The main purpose is to investigate the development of competencies and skills related to conceptual, historical and philosophical aspects of Modern and Contemporary Physics (FMC) in a Physics Degree course at a Public University at Ceará (Brazil) and implications of this training for the ENADE. Knowing that the National System of Evaluation of Higher Education (SINAES) is the program responsible for evaluating the educational quality of Higher Education Institutions (IES) in the country, being ENADE the main tool for evaluation of undergraduate courses in Brazil. We conducted an analysis seeking to understand what are the implications of ENADE in a Physics Degree course of a state public institution. Our research is based on qualitative aspects of an approach advocated by Bogdan and Biklen (1994) which values subjective, descriptive and interpretative aspects in the investigation. We used content analysis for the treatment of data according to Bardin's (2011) meanings. As a starting point, we analyzed official documents external (National Curriculum Guidelines for teacher training and for Physics courses) and internal (Pedagogical Project of the Degree Course in Physics of a state public institution), as well as the guidelines on the exams of ENADE, in order to identify the professional profile of a physicist, the contents, skills and abilities, focusing on historical and philosophical aspects of Modern and Contemporary Physics. In addition, interviews were conducted with teachers from the department of a degree course in Physics of a state public institution, seeking to identify the implications of ENADE in the course, to be precise, in its pedagogical practices. The investigated professors showed concerns with the results of the exam, since this is one of the criteria for calculating the CPC, responsible for the regulation of undergraduate courses; they emphasize that it is important to work with exam questions in order to familiarize students with this type of test and that the historical and philosophical aspects are worked on in the course. Problems of Modern and Contemporary Physics were selected from the ENADE editions, with emphasis on those that presented a historical and philosophical approach. It was found that such aspects are only used to contextualize the enunciation of the problem, generating distortions regarding the use of the history of science. Most of the problems analyzed explore only content skills, forgetting about other skills that are fundamental for the development of essential competences for the training of graduates in Physics, for example, the planning and development of different didactic experiences in Physics, recognizing relevant elements to appropriate strategies; the development or adaptation of didactic materials of different natures, identifying their formative, learning and educational objectives (BRASIL, 2001a, p. 5). So, this work can contribute to the knowledge of principles that underlie the ENADE, such as implications of its results in the degree courses in Physics, in addition to awakening reflections on professionals from the academic community (teachers, students and researchers), as the type of training they are offering to their students, how to rethink their teaching practices and consequently improve the quality of higher education.